Stress and Achievement of Cardiovascular Health Metrics: The American Heart Association Life's Simple 7 in Blacks of the Jackson Heart Study. Issue 11 (1 October 0207) - Brewer, LaPrincess C.; Redmond, Nicole; Slusser, Joshua P.; Scott, Christopher G.; Chamberlain, Alanna M.; Djousse, Luc; Patten, Christi A.; Roger, Veronique L.; Sims, Mario
Abstract : Background: Ideal cardiovascular health metrics (defined by the American Heart Association Life's Simple 7 [LS7]) are suboptimal among blacks, which results in high risk of cardiovascular disease. We examined the association of multiple stressors with LS7 components among blacks. Methods and Results: Using a community‐based cohort of blacks (N=4383), we examined associations of chronic stress, minor stressors, major life events, and a cumulative stress score with LS7 components (smoking, diet, physical activity, body mass index, blood pressure, total cholesterol, and fasting plasma glucose) and an LS7 composite score. Multivariable logistic regression assessed the odds of achieving intermediate/ideal levels of cardiovascular health adjusted for demographic, socioeconomic, behavioral, and biomedical factors. The LS7 components with the lowest percentages of intermediate/ideal cardiovascular health levels were diet (39%), body mass index (47%), and physical activity (51%). Higher chronic, minor, and cumulative stress scores were associated with decreased odds (odds ratio [OR]) of achieving intermediate/ideal levels for smoking (OR [95% confidence interval], 0.80 [0.73–0.88], 0.84 [0.75–0.94], and 0.81 [0.74–0.90], respectively). Participants with more major life events had decreased odds of achieving intermediate/ideal levels for smoking (OR, 0.84; 95% confidence interval, 0.76–0.92) and fasting plasma glucose (OR, 0.90; 95% confidence interval, 0.82–0.98). Those with higher scores for minor stressors and major life events were less likely to achieve intermediate or ideal LS7 composite scores (OR [95% confidence interval], 0.89 [0.81–0.97] and 0.91 [0.84–0.98], respectively). Conclusions: Blacks with higher levels of multiple stress measures are less likely to achieve intermediate or ideal levels of overall cardiovascular health (LS7 composite score), specific behaviors (smoking), and biological factors (fasting plasma glucose).